The accuracy of using vergence formula to screen myopia in children: a cross-sectional study - Yi, Zhen; Hong, Chang; Haikuo, Huang; Xinxin, Wang (Frontiers in Medicine, 2023)
Objective: To evaluate the accuracy of using the vergence formula to screen myopia in children and adolescents. Methods: This was a cross-sectional study conducted between December 2022 and May 2023 at the ophthalmology clinic of Beijing Tongren Hospital. A total of 336 children aged 6 to 12 years with refractive errors were selected according to the inclusion criteria. Biometric measurements, including axial length, corneal thickness, anterior chamber depth, corneal curvature, and lens thickness, were obtained using a biometer. The Calculated spherical equivalent (SE) was then calculated using the vergence formula. Cycloplegic refraction was performed after paralysis of the ciliary muscle, and the subjective SE was recorded. A diagnosis of myopia was made if the subjective SE was ≤ -0.50 diopters.Results: The AL/CR, subjective SE, and calculated SE were not normally distributed (p < 0.05). The AL/CR value was 3.08 (2.81, 3.27), the SE was -1.60 D (-6.00 D, 3.75 D), and the calculated SE was